2007
DOI: 10.2500/ajr.2007.21.3029
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Chronic Rhinosinusitis-Associated Sinonasal Ciliary Dysfunction

Abstract: CRS is a common debilitating disease principally affecting sinonasal epithelial function with a resultant diminution of mucociliary transport. Presently, little is known about how this disease process affects the sinonasal epithelial ciliated cells. Our data suggest that ciliary response to environmental insults is blunted in a reversible manner in CRS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 70 publications
3
39
0
4
Order By: Relevance
“…In 1 study, ciliated cells that were removed from the inflammatory milieu of CRS regained their ability to be stimulated and again functioned in a normal fashion. 495 Therefore, most effort clinically should be in treating the underlying CRS, as opposed to treating the dysfunctional cilia separately. Topical antimicrobial therapy results in not only symptomatic improvement, but in 1 study of 10 patients also showed an increase in CBF back to expected levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1 study, ciliated cells that were removed from the inflammatory milieu of CRS regained their ability to be stimulated and again functioned in a normal fashion. 495 Therefore, most effort clinically should be in treating the underlying CRS, as opposed to treating the dysfunctional cilia separately. Topical antimicrobial therapy results in not only symptomatic improvement, but in 1 study of 10 patients also showed an increase in CBF back to expected levels.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and acquired defects in mucociliary flow are associated with a high incidence of CRS, and these entail variations in viscosity and ciliary activity. [493][494][495][496] Beneath the mucus reside the epithelial cells (ECs), which are linked by tight and adherens junctions. Tight and adherens junctions comprise the apical junctional complex (AJC), creating a relatively impermeable barrier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapy addressed to the nasal MCC can be of benefit to the MCC of the lower respiratory tract [8].…”
Section: Viscosity Therapymentioning
confidence: 99%
“…Mucus layer is moved up and over the larynx and then is swallowed to the stomach. Stomach acid generally inactivates the bacteria [8].…”
Section: Functions Of MCCmentioning
confidence: 99%